Virulence of isolates of Metarhizium anisopliae and their field efficacy on Hypothenemus hampei - BERNAl-U., MARTHA GLADYS; BUSTILLO-P., ALEX ENRIQUE; POSADA-F., FRANCISCO JAVIER (Revista Colombiana de Entomología, 1994)
Fourteen isolates of Metarhizium anisopliae were tested for pathogenicity on adults of the coffee berry borer, Hypothenemu hampei under laboratory conditions (T=25 ± 3°C, R.H.=90%) using a concentration of 1 x 107 conidia/ml. All the tested isolates were pathogenic against the borer, however, their virulence was variable. Mortality fluctuated between 32.5% for isolate Ma 9211 to Ma 9101. Average time of mortality after 8 days was also variable with a minimum of 3.4 days for Ma 9101 an a maximum of 5.7 days for Ma 9107. Field trials in coffee plantations were carried out with isolates Ma 9108, Ma 9003, and Ma 9101, which in laboratory pathogenicity tets all reached more than 84% mortality. A dose of 1.5x10’ conidia/branch of 50 berries was evaluated with every isolate. Mortality varied from 31.1% for Ma 9108 to 43.1% for Ma 9101, however, no significant differences were detected (P=0.05) between isolates. This study reports for the first time the effect of M. anisopliae on coffee berry borer populations under field conditions and the importance of isolate selection of entomopathogens before considering them in a biological control program.